2019
DOI: 10.25156/ptj.v9n1y2019.pp23-25
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Action of Alfalfa (Medicago sativa) Leaves Powder on Type II Diabetic Patients

Abstract: Type II diabetes is a common metabolic disorder that is specified by hyperglycemia resulting from defects in insulin action. Alfalfa (Medicago sativa) is a medicinal plant (leaves, flower, and seeds) used traditionally as antidiabetic. This study is designed to investigate the short-term antidiabetic action of alfalfa leaves powder in patients with Type II diabetes mellitus. 12 volunteers suffering from type II diabetes were undertaken besides 12 healthy individuals. The subjects were divided into four groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…As antidiabetic agents, the leaves of Medicago have been used traditionally to reduce plasma glucose levels in diabetic subjects [ 45 , 46 ]. In this investigation, the accumulation of nitrogen compounds enhanced by KNO 3 priming increased the antidiabetic activity of Medicago sprouts extracts, since the GI decrease sharply mainly in Medicago interexta compared to others sprouts in response to KNO 3 priming.…”
Section: Discussionmentioning
confidence: 99%
“…As antidiabetic agents, the leaves of Medicago have been used traditionally to reduce plasma glucose levels in diabetic subjects [ 45 , 46 ]. In this investigation, the accumulation of nitrogen compounds enhanced by KNO 3 priming increased the antidiabetic activity of Medicago sprouts extracts, since the GI decrease sharply mainly in Medicago interexta compared to others sprouts in response to KNO 3 priming.…”
Section: Discussionmentioning
confidence: 99%
“…In consideration of the fact that oxidative stress induced by exposure to environmental pollutants such as mercury may lead to kidney and liver poisoning, researchers believe that antioxidant compounds can play a protective role against these pathological conditions [ 7 ]. Alfalfa, Medicago sativa L., is one of the most famous traditional medicinal plants used to cure and prevent many diseases [ 8 ]. Alfalfa contains vitamins (A, B1, B6, B12, C, D, E, and K), amino acids, sugars, proteins, minerals (Fe, Zn, Cu, Al, B, Cr, Co, Mn, Mo, Se, Si, Na, Ca, P, K, and Mg), and other nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa contains vitamins (A, B1, B6, B12, C, D, E, and K), amino acids, sugars, proteins, minerals (Fe, Zn, Cu, Al, B, Cr, Co, Mn, Mo, Se, Si, Na, Ca, P, K, and Mg), and other nutrients. Due to its richness in vitamins and phytoestrogens, this plant is used as a food additive in several countries [ 8 ]. Phytochemical studies indicated that this plant contains a variety of secondary metabolites including flavonoids, alkaloids, phytoestrogens (coumestrol, daidzein, genistein, and pyocyanin), and coumarins as potent antioxidants [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also stimulates insulin secretion from the islets of healthy and diabetic people if taken with meal. 22 Despite the traditionally known hypoglycaemic activity of alfalfa both in animals and humans, so far, only a few investigations have been carried out to prove this issue. In the present study, in vitro trans -differentiation of mouse bone marrow mesenchymal stem cells (MSCs) into pancreatic β-like cells (insulin-producing cells; IPCs) under the influence of alfalfa flower and leaf extract was investigated for the first time.…”
Section: Introductionmentioning
confidence: 99%